中白公益短片设计-跨越梦想的鸿沟 - Li, Yuhang (БНТУ, 2022)
The project deepen the theme of “Dream Global” and introduce the term “dream” to record people's answers to their dreams and the direction they need to work hard. The idea of the project development is to show the glory, while achieving public welfare goals, deepen mutual trust between the two countries, go to peaceful development, and create a prosperous future.